EFFECT OF FEEDING COMPLETE DIET SUPPLEMENTED WITH EXOGENOUS FIBROLYTIC ENZYME COCKTAIL OR ARTEMISIA ABSINTHIUM L. HERB ALONE AND IN COMBINATION ON ENERGY METABOLIC PROFILE OF LAMBS - Yasir Afzal Beigh; Abdul Majeed Ganai; Shoukeen Muzamil (Exploratory Animal and Medical Research, 2017)
To augment sheep productivity in temperate regions by improving feed utilization efficiency, the present study was planned to assess the effect of supplementation of exogenous fibrolytic enzyme cocktail and Artemisia absinthium L. (locally known as Afsanteen) herb alone and in combination as feed additives in oats straw based complete diet on energy metabolic profile in crossbred lambs. Twenty crossbred lambs were randomly divided into four groups of 5 each and were fed individually for a period of 90 days. Animals in all the groups were offered complete feeds based on oats straw 40 parts, mixed grass hay 20 parts and concentrate mixture 40 parts. The complete feeds were supplemented either alone with exogenous fibrolytic enzyme cocktail (T1 ) @ 6 g/kg DM or Afsanteen herb (T2 ) @ 4.5% of DM and combination of the two feed additives (T3 ), whereas the complete feed without any supplementation served as control (T0 ).Blood monitoring was carried out at the start and subsequently at monthly intervals of the experiment. Blood glucose was estimated in whole blood immediately after collection and rest were subjected to serum harvesting to analyze for non-esterified fatty acids (NEFA) and β-hydroxybutyrate (BHB) levels. There were no significant differences for overall blood glucose, serum NEFA and BHB levels among the treatment groups while significant (P<0.01) effect of period were recorded. It may be concluded that supplementation of exogenous fibrolytic enzyme cocktail and A. absinthium L. herb alone or in combination to complete feed is possible for intensive rearing of lambs without any adverse effect on energy metabolic profile.